INTERFERENCE OF ALLELOCHEMICALS OF THREE WEED SPECIES IN SEED GERMINATION, SEEDLING GROWTH, UPTAKE OF PHOSPHORUS AND ZINC IN THREE VARIETIES OF PADDY - Chakravarthy, S.; Sharma, K.; Rao, P.B.; Pandey, N. (Ecoprint: An International Journal of Ecology, 2004)
Effect of the extracts of three dominant weed species viz., Phalaris minor Retz., Chenopodium album L. and Polygonum hydropiper L. were examined on the seed germination, seedling growth and nutrient uptake (32p and 65Zn) in Swarna, Jaya and N-359 varieties of paddy (Oryza sativa L.). The maximum reduction in terms of seed germination, radicle and plumule length and total seedling dry weight was caused by P. hydropiper and in terms of radicle and plumule dry weight by C. album. Among the three different varieties irrespective of weed extracts, Swarna was resistant in seed germination, plumule length, radicle, plumule and total seedling dry weight and Jaya was only for radicle length, whereas N-359 was found susceptible in length and total seedling dry weight. The allelochemicals also interfered in gradual decrease in uptake of both 32P and 65Zn with increasing concentration of the chosen three weed extracts, both in root and shoot. Among the three varieties of paddy, Jaya was susceptible for 32P but resistant for 65Zn whereas N-359 was resistant for both the ions. Water soluble phenolics such as gallic, protocatechuic, p-hydroxybenzoic, caffeic and vanillic acids were identified from these extracts. The inhibition may be due to these phenolics and other unidentified secondary metabolites in weed extracts.Key words: Germination, nutrient uptake, paddy, phenolics, seedling growth, weed extracts.Ecoprint Vol.11(1) 2004.